A U3 snoRNP protein with homology to splicing factor PRP4 and G beta domains is required for ribosomal RNA processing. - Jansen, R (1993)
Yeast fibrillarin (NOP1) is an evolutionarily conserved, nucleolar protein necessary for multiple steps in ribosome biogenesis. Yeast mutants lacking a functional NOP1 gene can be complemented by human fibrillarin but are temperature sensitive for growth and impaired in pre-rRNA processing. In order to identify components which interact functionally with human fibrillarin in yeast, we isolated extragenic suppressors of this phenotype. One dominant suppressor, sof1-56, which is allele-specific for human fibrillarin and restores growth and pre-RNA processing at 35 degrees C, was cloned by in vivo complementation. The wild-type allele of SOF1 is essential for cell growth and encodes a novel 56 kDa protein. In its central domain, SOF1 contains a repeated sequence also found in beta-subunits of trimeric G-proteins and the splicing factor PRP4. A single amino acid exchange in the G beta-like repeat domain is responsible for the suppressing activity of sof1-56. Indirect immunofluorescence shows that SOF1 is located within the yeast nucleolus. Co-immunoprecipitation demonstrates the physical association of SOF1 with U3 small nucleolar RNA and NOP1. In vivo depletion of SOF1 leads to impaired pre-rRNA processing and inhibition of 18S rRNA production. Thus, SOF1 is a new component of the nucleolar rRNA processing machinery.